Photochemical Synthesis of Azaheterocycles - Tanoury, Gerald J. (Synthesis, 2016)
Synthetic organic photochemistry is a field that continues to offer unique routes to organic structures not typically accessed from thermal reactions. In this review, the photochemical synthesis of five-, six-, seven-, and eight-membered-ring azaheterocycles, as well as some aza-macrocycles, is discussed. The discussion will focus on methods where heterocycle formation occurs during or as a result of a photochemical event. Reaction mechanisms will be discussed also, as these provide a rationale for understanding the synthetic results.1 Introduction2 Five-Membered Rings2.1 Cyclization Reactions2.2 Cycloadditions2.3 From Aromatic and Vinyl Azides2.4 earrangements2.5 Other Individual Methods3 Six-Membered Rings3.1 Cyclization Reactions3.2 Isocyanide Insertions3.3 Cycloadditions4 Seven-Membered Rings and Larger5 Conclusion
Keywords: azaheterocycles; photocycloaddition; photocyclization; photorearrangement; photocatalyst